Adolescent Determinant Who Makes Sexual Pre Marriage Relations in Simalungun, Indonesia: Cross-Sectional Study - Pinondang Hotria Siregar; Ricard Fredrik Marpaung (International Journal of Psychosocial Rehabilitation, 2020)
Teenagers have lack of knowledge about health and sexuality reproductive. Most of teenagers do not have access to get information and service about reproductive. Information is usually obtained from peers or the media which is inaccurate. Preliminary study was in Simalungun District from July until September 2019. The purpose of the study was to analyze the relationship among determinant of adolescent sexually engaging in pre marriage sex. The research design of this study is analytical research with a cross-sectional approach. The subject used in this research were high school adolescents with a large sample of 166 people, using Simple Random Sampling method. Data collection used in this study was primary data and analyzed using the Chi-Square test. Results of the study analyzed with Chi-Square obtained (P-value <α 0.05) there was a relationship between knowledge, the relationship between parents and adolescents, self-esteem, the role of peers, understanding of the religion level (religiosity), the role of the mass media with students’ attitude in pre marriage sexual relations. As a teenager must be able to manage the information and knowledge obtained about pre marriage sexual relations correctly. During their development as teenagers, students should filter any information that violates social and religious norms about pre marriage sexual relations.